Observing Social Exclusion Leads to Dehumanizing the Victim - Park, Yeong O.; Park, Sang H. (Frontiers in Psychology, 2015)
We hypothesized that observing social exclusion would influence observers’ judgments of the humanness of its victims and perpetrators. Specifically, we speculated that people would attribute victims and perpetrators to lower and higher mental capacities, respectively. Participants observed a simulated computer-based ball tossing game in which one of the players was either ostracized or not. They then rated the game players on traits associated with two dimensions of humanness, namely Human Nature (HN) and Human Uniqueness (HU). Overall, participants who witnessed an exclusion game judged the victim as less human on both domains compared to one of the perpetrators as well as to a player in the control condition. The perpetrator was attributed higher HN, but not significantly higher HU, compared to the control player. In addition, the less HN attributes a target was assigned, the more she was expected to be vulnerable to exploitation. On most of the other measures of target impression, however, the victim was rated more favorably than the perpetrator. The findings imply that social exclusion victims are often subtly derogated compared to the perpetrators, even while they are also more positively evaluated otherwise.